Pengaruh Motivasi, Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan Rumah Sakit Umum Daerah Wangaya Kota Denpasar - Ni Ketut Murdani; Ni Luh Ketut Ayu Sudha Sucandrawati; I Dewa Nyoman Usadha (Universitas Mahendradatta Denpasar, 2018)
The success of the company is strongly influenced by the performance of its employees. Good performance is the optimal performance, that is, performance that conforms to the organization's standards and supports the achievement of organizational goals. Each company will strive to always improve the performance of its employees in order to achieve the goals set by the company.The purpose of this study are: 1) To determine the effect of motivation on employee performance Wangaya Denpasar Hospital; 2) To know the influence of leadership on employee performance of RSUD Wangaya Denpasar City; 3) To know the influence of work discipline on employee performance of Wangaya Hospital Denpasar City; and 4) To find out whether the motivation, leadership and work discipline affect together on the performance of employees of Wangaya Hospital Denpasar City. Data Analysis Method used in this research is quantitative data analysis and analyze by using program of SPSS ( Statistical Package for Social Science) for windows version 21.The result of this research is that the motivation has no significant effect to the employee performance at RSUD Wangaya Kota Denpasar of 0,111 or 11% where significant value 0,106 or bigger than level of significant (α) 0,05 Leadership significant to employee performance at RSUD Wangaya Denpasar city sebersar 0,210 or 21% where significant value 0.000 or smaller than level of significant (α) 0,05. Work discipline has no significant effect on employee performance at RSUD Wangaya Kota Denpasar of 0,051 or 5% where significant value 0,477 or bigger than level of significant (α) 0,05. Motivation, leadership and work discipline together affect the performance of employees of Wangaya Hospital Denpasar City of 0.67 or 67% of the rest by 33% influenced by the variable not examined in this study. Where the significance value is 0.000 or smaller than the 0.05 level of significant (α) 0,05.